Influence of Spiral Nematodes (Scutellonema spp.) on Maize Performance and Growth under Natural Field Infestation in Mwea, Kenya - Samuel Maina; Rossa Nyoike Ng’endo (International Journal of Agronomy)
Maize (Zea mays L.) is a significant food security crop in Kenya and it serves as the main source of nutrition and calories among the small-holder farmers. The overall maize yields per hectare have been fluctuating in the past few years posing a great risk to food security. Among the stress factors associated with maize yield loss include plant-feeding nematodes. In this regard, this study was conducted to evaluate the impacts of plant-parasitic nematodes specifically Scutellonema spp. under field conditions on maize performance in Mwea, Kenya. The field trials were laid out in a randomized complete block design with each treatment comprising of four replicates. The treatments included maize plots without nematicide (MPWN) and control plots treated with nematicide. The experiments were conducted in two trials. Soil samples were taken at a 0–20 cm depth at monthly intervals during 2018–2019. During the two trials, MPWN recorded significantly lower plant height and number of leaves per plant. Correlation analysis revealed a significant negative relationship between Scutellonema abundance with leaf area index, plant height, and number of functional leaves in MPWN during the 2019 trial. This implies that high population of Scutellonema perhaps has the potential to affect leaf area index, plant height, number of leaves per plant, which are aspects that in turn influence maize productivity. Therefore, holistic sustainable management practices to control Scutellonema spp. in maize fields such as use of organic amendments, resistant maize cultivars, and antagonistic organisms are crucial in order to alleviate negative impacts linked to Scutellonema infestation.